Pemanfaatan dan Pengelolaan Keanekaragaman Tumbuhan di Persawahan berbasis Kearifan Lokal Masyarakat Adat Using Kemiren, Banyuwangi - Alda Alfiah Dwi Nandini; Agus Prasetyo Utomo; Ika Priantari (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Plant diversity in agricultural landscapes plays a vital role in maintaining ecosystem sustainability and local food security. This study aims to analyze the utilization, management, and conservation of plant diversity by the Using Indigenous community in Kemiren Village, Banyuwangi. A qualitative approach was used, with data collected through interviews, observation, and documentation. A total of 10 informants (2 key informants and 8 recommended informants) were selected using purposive sampling and snowball sampling techniques. The informant selection criteria were traditional elders, local farmers, and the Using community of Kemiren Village who possessed local knowledge regarding the types and uses of plant diversity found in their rice fields. Data validity was tested using cross-reference information, repeated information, and data triangulation. Data analysis was conducted qualitatively. The research results show that the community uses 23 plants for food, medicine, traditional ceremonies, animal feed and building materials. Plant management is carried out through land clearing, seed preparation, planting, maintenance, and harvesting. The steps combining traditional and modern technique, and supported of local rituals such as labuhan and adeg-adeg.  Conservation practices include the use of organic fertilizers, post-harvest waste management, crop diversification, natural pest control, and water management based on local wisdom. The integration of local knowledge and conservation practices has been shown to play a role in conserving biodiversity, supporting food security, and promoting sustainable agriculture.